Phenotype and molecular characteristics in 45 Chinese children with 5α‐reductase type 2 deficiency from South China. (7th May 2015) - Cheng, Jing; Lin, Ruizhu; Zhang, Wen; Liu, Guochang; Sheng, Huiying; Li, Xiuzhen; Zhou, Zhihong; Mao, Xiaojian; Liu, Li
Summary Context Affected by steroid 5α‐reductase type 2 deficiency (5α‐RD2), 46, XY individuals present divergent phenotypes characterized by undervirilization of male external genitalia. To identify the disorder, mutational analysis of 5α‐reductase type 2 gene (SRD5A2) is a reliable approach. The genotype–phenotype relationship has not been elucidated. Objective To improve the diagnosis and expand the knowledge of the disease, we collected and analysed relevant data of clinical diagnosis, biological investigation and molecular determination in 45 children with the SRD5A2 gene mutations from South China in our centre. Subjects and methods We studied a cohort of 45 Chinese children with SRD5A2 gene mutations. Results Isolated microphallus (35·6%) and microphallus associated with various degrees of hypospadias (55·6%) were frequent phenotype. Female external genitalia with clitoromegaly (8·9%) were rare. 16 of 18 (88·9%) cases had hCG‐stimulated T/DHT ratio above 10. In 45 patients, we identified 15 different mutations. Five have never been described: p.His90ThrfsX31, p.Gly21Arg, p.Gly149Asp, p.Arg145Leu and p.Gly66Arg. The p.Arg227Gln mutation was detected in 41 (91·1%) patients. The p.Leu89Val polymorphism was found in 38 (84·4%) patients. Homozygous mutations were presented in 16 (35·6%) patients, compound heterozygous mutations in 20 (44·4%) patients, compound heterozygous mutations alone with the p.Leu89Val polymorphism in nine (20·0%) patients. Exons 1 and 4 were most affected, and the number of mutant alleles per exon was 78·1% and 12·2%, respectively. Conclusions The study demonstrated a wide spectrum of phenotypes, biological profiles and genotypes in the children with 5α‐RD2 from South China. The heterozygous mutation p.Arg227Gln is presumably a hot spot mutation and suggests a founder effect in the population of South China that may explain a moderate phenotype among our patients. Our report provides new insights into the molecular mechanism of 5α‐RD2 and help to the diagnosis and treatment of this disease.